Identification of complex admittance functions using 2D-URANS models: Inflow generation and validation on rectangular cylinders. Issue 208 (January 2021) - Li, Weilin; Patruno, Luca; Niu, Huawei; de Miranda, Stefano; Hua, Xugang
Abstract: The evaluation of the aerodynamic admittance functions is a key step in the calculation of bridges and towers buffeting response. For streamlined bodies, such functions can be well approximated by the closed form solution developed by Sears. For bluff bodies, the evaluation of the admittance function still represents an open problem: experimental procedures require the use of grid turbulence or active wind tunnels. In the first case, a number of interrelated factors contribute to the obtained results while, in the second case, the experimental apparatus is of considerable complexity. In this paper, the use of Computational Fluid Dynamics for the evaluation of complex admittance functions is analyzed. Firstly, a discussion regarding the characterization of the flow in active wind tunnels and its reproduction in numerical simulations is presented. Such aspect has been often overlooked in previous studies, in which experimental procedures have been mimicked, so not taking full advantage of the CFD approach. Then, rectangular cylinders with aspect ratio ranging between 4 and 16.67 are studied by means of 2D URANS. It is shown that while 2D URANS usually lead to acceptable results, they can prove inaccurate in specific cases. Additional LES simulations led to a good matching of the experimental data. Highlights: The extraction of Aerodynamic Admittance Functions by CFD analyses is described. Methods to generate gusts in wind tunnels and CFD are compared. Aerodynamic Admittance is calculated with 2D URANS for a set of rectangular cylinders. A LES is performed on the rectangular cylinder with aspect ratio equal to 6.